IDENTIFYING THE UNDERSTANDING OF THE PEOPLE LIVING WITH HIV REGARDING PREVENTING HIV TRANSMISSION IN JAYAPURA CITY, INDONESIA - Ramban, Windy Marini; Assa, Inriyanti; Mamoribo, Sherly N.; Asmuruf, Frans; Asriati, Asriati; Yufuai, Agustina R (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2024)
Background: Human Immunodeficiency Virus is a virus that can attack and reduce the human immune system, causing various symptoms of the disease called AIDS. Prevention is very important for people living with HIV in order to break the chain of HIV transmission. The aim of this research is to identify the understanding of the people living with HIV regarding preventing HIV transmission in Jayapura City.Method: The type of research is quantitative analytic with a cross sectional design. The research was conducted at the Waena and Hebeybhulu Yoka Community Health Centers in June-July 2023. The respondents in this study were PLWHA who came to take medicine at the community health centers. Using a saturated sampling technique, there were 63 respondents. The measuring instrument used was a questionnaire, data was analyzed univariately and bivariately using the chi-square test (α < 0.05).Results: The majority of respondents were adults (92.1%), the majority of gender was female (58.7%), high education (79.4%), not working (54.0%), the majority of marital status was unmarried. (52.4%), information about HIV through print media (81%), direct media from health workers (74.6%), good understanding regarding preventing HIV transmission (69.8%). The results of the chi-square test showed a relationship between understanding of PLWHA and actions to prevent HIV transmission in Jayapura City (p-value = 0.005 < 0.05).Conclusion: PLWHA will undergo regular treatment and take preventive measures so as not to infect partners or other people.